Derivas epistemológicas y metodológicas de un estudio sobre procesos de movilidad y migración transnacional en América Latina - Perret Marino, María Gimena (Comparative Cultural Studies: European and Latin American Perspectives, 2017)
This paper aims to critically reflect on the epistemological and methodological challenges involved in the study of contemporary mobility and migration processes. We take as starting point, our own research on Chilean migration in Argentina so our goal in this paper is to raise some thoughts regarding ethnographic field work, its limits, specifically in investigations in which an intensive ethnographic practice in a specific territory is not a task easy to achieve.